2014
DOI: 10.5861/ijrsll.2014.700
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the effect of the model of metacognitive instruction on the listening performance of EFL learners

Abstract: This study sought to explore the effect of two different models of metacognitive instruction on the listening performance of EFL learners in Iran. The participants were 90 intermediate EFL listeners in three groups, ranging from 20 to 26 years of age. The participants in experimental group one (n = 30) went through a ten-week intervention program that involved the linear instruction of ten metacognitive strategies, with its focus on planning, monitoring, and evaluation. The participants in experimental group t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Compared to the students in the contrast group, the learners in the treatment group also became more proactive learners by watching movies in English, downloading the audio materials, listening to them, and reading the texts aloud outside the classroom, for example. Discussions through special sessions seemed to play a significant role for developing their awareness and learning (e.g., Fahim & Fakhri Alamdari, 2014;Vandergrift & Goh, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to the students in the contrast group, the learners in the treatment group also became more proactive learners by watching movies in English, downloading the audio materials, listening to them, and reading the texts aloud outside the classroom, for example. Discussions through special sessions seemed to play a significant role for developing their awareness and learning (e.g., Fahim & Fakhri Alamdari, 2014;Vandergrift & Goh, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Although very few studies on metacognitive instruction in oral communication have been conducted, several researchers have examined the effectiveness of metacognitive instruction in listening classes in both English as a Second Language (ESL) and EFL contexts (e.g., Chen, 2010;Cross, 2011;Goh & Taib, 2006;Graham & Macaro, 2008;Fahim & Fakhri Alamdari, 2014;Rahimi & Katal, 2013;Vandergrift & Tafaghodtari, 2010). Research shows that: (1) learning strategies (including metacognitive strategies) influence learning outcomes and self-efficacy (Graham & Macaro, 2008;Rahimi & Katal, 2013); (2) Metacognitive instruction influences listening comprehension (Cross, 2011;Goh & Taib, 2006;Vandergrift & Tafaghodtari, 2010); (3) Metacognitive instruction is effective especially for less skilled listeners (e.g., Cross, 2011;Kobayashi, 2018); (4) Metacognitive instruction affects learning outcomes (Goh & Taib, 2006); and (5) Metacognitive instruction improves metacognitive awareness, perceived use of listening strategies, and speaking ability (Rahimi & Katal, 2013).…”
Section: Research In Metacognitive Instruction In Oral Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Now, there is a respectable body of empirical evidence both in EFL (e.g. Fahim & Fakhri Alamdari, 2014;Goh & Hu, 2013;Rahimi & Katal, 2012 and ESL (e.g. Vandergrift, 2002Vandergrift, , 2003Vandergrift & Tafaghodtari, 2010) contexts bearing testimony to the effectiveness of L2 listening metacognitive instruction.…”
Section: Introductionmentioning
confidence: 99%
“…Research into listening from this vantage point is a relatively nascent undertaking (Goh, 2008), however. It has been shown that metacognitive instruction benefits less--skilled L2 listeners more (Cross, 2010;Goh & Tiab, 2006), is positively related to learners' motivational aspects (Baleghizadeh & Rahimi, 2011;Vandergrift, 2003Vandergrift, , 2005, and promotes L2 listening performance (e.g., Al--Alwan, Asassfeh, & Al--Shboul, 2013;Bozorgian, 2012;Coskun, 2010;Fahim & Fakhri Alamdari, 2014;Goh & Hu, 2013;Shirani Bidabadi & Yamat, 2011;Vandergrift, Goh, Mareschal, & Tafaghodtari, 2006).…”
Section: Introductionmentioning
confidence: 99%